An Efficient Method for Constructing Cyclic β-Amino Acids Bearing Quaternary Stereocenters - Qin, Shuanglin; Liu, Tongtong; Luo, Yunhao; Yan, Jun; Kang, Hong; Jiang, Shende; Yang, Guang (Synlett, 2019)
This paper describes an efficient method for constructing cyclic β-amino acids bearing quaternary stereocenters. NaHMDS-promoted asymmetric α-alkylation was employed to obtain the key intermediates with quaternary stereogenic centers, which were subsequently reduced by NaBH4 in 10% methanol in THF, with high yields and high diastereoselectivities. By removing the allyl ester group and the chiral auxiliary, the corresponding cyclic β-amino acid hydrochlorides were finally obtained.
Keywords: β-amino acids; quaternary stereocenters; asymmetric alkylation; sulfimines; diastereoselectivity